Manganese-cerium aerogel multifunctional catalytic material as well as preparation method and application thereof
By designing a manganese-cerium-loaded airgel molecular sieve composite multifunctional catalytic material, the problems of conventional catalysts in gas-solid fluidization systems such as heavy specific gravity, poor moisture resistance, and difficulty in regulating mass and heat transfer properties have been solved, and waste liquid treatment has been achieved. High efficiency and low energy consumption pyrolysis effect.
Patent Information
- Application Number
- CN202411450477.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
When conventional catalysts treat waste liquid in gas-solid fluidized systems, there are problems such as large specific gravity, poor humidity resistance, and difficult to regulate mass and heat transfer performance, resulting in low catalytic efficiency, poor stability and disordered reactions.
Develop a multi -functional catalytic material of gas gel molecular sieve compound manganese -loaded gas gel molecules. By designing its inner and outer structure, it improves the performance of the proportion, humidification, and mass transmission heat transfer, and realizes the stability and activity improvement of the catalyst.
The catalytic material shows good catalytic cracking and oxidation capabilities under high humidity and gas-solid fluidized state, can effectively reduce reaction energy consumption and macroscopic pyrolysis temperature, and achieve high-efficiency and low-energy consumption pyrolysis of waste liquid.
Smart Images

Figure CN119327446A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of waste liquid treatment, and in particular to a manganese-cerium aerogel multifunctional catalytic material and a preparation method and application thereof, which are applied to the cracking and oxidation of organic matter contained in waste liquid in a gas-solid fluidization system. Background Art
[0002] In today's rapidly developing industrialization process, the treatment of chemical waste liquid has become an important issue that cannot be avoided in environmental protection and industrial sustainable development. Chemical waste liquid, especially waste from the fields of medicine, textiles, petrochemicals, etc., has complex composition, high chemical oxygen demand (COD) and biochemical oxygen demand (BOD), rich organic matter content, and is flammable, explosive, corrosive and reactive, which poses great challenges to treatment. If these waste liquids are discharged directly without proper treatment, they will not only cause serious damage to aquatic ecosystems, but may also accumulate through the food chain and ultimately affect human health.
[0003] For the treatment of such high-concentration organic waste liquid, traditional methods such as physical precipitation, chemical oxidation, and biodegradation are often limited in their widespread application due to problems such as low treatment efficiency, high cost, or secondary pollution. In recent years, with the increasingly stringent environmental regulations and the continuous advancement of environmental protection technology, it is particularly important to explore efficient, economical, and environmentally friendly waste liquid treatment technologies. Among them, the use of fluidized bed reaction systems for the cracking and oxidation treatment of waste liquids has gradually become a research hotspot because it can achieve efficient conversion of organic matter. The fluidized bed reaction system is a reactor that fluidizes solid particles through gas or liquid to enhance the efficiency of mass transfer and heat transfer. In this system, the waste liquid is atomized and fully contacted with the catalyst in the fluidized state, which can promote the cracking and oxidation reaction of organic matter under normal pressure conditions, and finally convert it into harmless inorganic small molecules such as carbon dioxide and water. This treatment method can not only effectively reduce the organic content in the waste liquid, but also reduce the emission of harmful substances, with high environmental benefits and potential economic value. However, conventional catalysts face many challenges when used in gas-solid fluidization systems to treat waste liquids. First, due to the large specific gravity of the catalyst, its gas-solid fluidization performance in the fluidized bed is poor, and it is difficult to maintain a stable fluidized state, which affects the catalytic efficiency. Secondly, the catalyst has poor moisture resistance. In a high humidity environment, its activity is easily reduced or even deactivated, resulting in a significant reduction in the treatment effect. In addition, the mass transfer and heat transfer performance of conventional catalysts during the reaction process is difficult to effectively regulate, and the reaction often presents a disordered state, which not only affects the conversion efficiency of organic matter, but also may trigger side reactions and produce new pollutants. Therefore, the development of a new catalytic material to overcome the above-mentioned problems of conventional catalysts in the treatment of waste liquid in a gas-solid fluidized system has become a key technical problem that needs to be solved in the current waste liquid treatment field. In particular, how to optimize the catalyst's specific gravity, moisture resistance, mass transfer and heat transfer performance through material design, and how to improve the catalyst's stability and catalytic activity, are the core directions of the research and development of new catalytic materials. In this context, the proposal of a manganese-cerium-loaded aerogel molecular sieve composite multifunctional catalytic material provides new ideas and possibilities for the efficient treatment of chemical waste liquid. Summary of the invention
[0004] Technical problems solved: In response to the above technical problems, the present invention provides a manganese-cerium aerogel multifunctional catalytic material and a preparation method and application thereof, which has a wide range of application environments and few inherent limitations.
[0005] Technical solution: A method for preparing a manganese cerium aerogel multifunctional catalytic material, the preparation steps comprising: (a) uniformly stirring tetraethyl orthosilicate, ethanol and water, wherein the molar ratio of tetraethyl orthosilicate, ethanol and water is n(TEOS):n(EtOH):n(H2O)=1:(3-12):(3-8), adjusting the pH to 2-3, and then hydrolyzing to obtain a silica sol; (b) dissolving two metal salts, manganese acetate and cerium nitrate, in water, wherein the corresponding oxides formed by the metal salts after calcination account for 2wt.%-30wt.% of the mass of the aerogel carrier, and then adding the mixed solution to the silica sol and stirring, adjusting the pH to 6-8, and standing at room temperature to obtain a gel; (c) preparing an aging solution with tetraethyl orthosilicate and ethanol, wherein the volume ratio is V(ETOH) / V(TEOS)=(4-10):1, pouring the solution into the gel for aging, and then replacing it with n-hexane, and then grading it. (d) immersing the aerogel in an acetic acid solution and stirring to etch the metal oxide on the surface of the aerogel, washing the obtained sample with deionized water until the filtrate is neutral, and drying it in an oven; (e) dissolving tetrapropylammonium hydroxide and urea in water, adding aluminum isopropoxide and stirring at room temperature, wherein the molar ratio of aluminum isopropoxide, tetrapropylammonium hydroxide, water and urea is n(AIP):n(TPAOH):n(H2O):n(urea)=1:(5-20):(800-3000):(20-80), spraying the obtained solution with aerogel powder, standing at room temperature, and then transferring the mixture to a polytetrafluoroethylene reactor liner, loading it into the reactor and placing it in an oven for hydrothermal crystallization, followed by washing, suction filtration, drying and calcining to obtain an aerogel molecular sieve composite multifunctional catalytic material loaded with manganese and cerium.
[0006] Preferably, in the above step (a), the molar ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is (TEOS):n(EtOH):n(H2O)=1:4:4; the reagent for adjusting pH is 0.1-1 mol / L dilute hydrochloric acid; the hydrolysis temperature is 25-60°C, and the hydrolysis time is 0.5-5h;.
[0007] Preferably, the reagent for adjusting pH in the above step (b) is 0.1-2.5 mol / L dilute ammonia water.
[0008] Preferably, the volume ratio of the aging solution in the above step (c) is V(ETOH) / V(TEOS)=4:1; the aging temperature is 25-70°C, and the aging time is 24-72h; the replacement temperature is 25-60°C, and the time is 9-24h; the gradient drying temperature is 2-4 points within 50-200°C, and the drying time at each temperature point is 1-4h; the calcination temperature is 400-700°C, and the insulation time is 4-6h.
[0009] Preferably, in the above step (d), the stirring time is 20-120 min; the drying temperature is 60-120° C., and the drying time is 8-12 h.
[0010] Preferably, in the above step (e), the molar ratio of aluminum isopropoxide, tetrapropylammonium hydroxide, ionized water and urea is n(AIP):n(TPAOH):n(H2O):n(urea)=1:10:1500:40; the stirring time is 1-24h; the standing time at room temperature is 3-15h; the hydrothermal temperature is 80-180°C, and the hydrothermal time is 9-72h; the drying temperature is 80-120°C, and the drying time is 8-12h; the calcination temperature is 400-600°C, and the calcination time is 3-6h.
[0011] The manganese-cerium aerogel multifunctional catalytic material obtained by the above preparation method.
[0012] The above-mentioned manganese-cerium aerogel multifunctional catalytic material is used in the cracking and oxidation of organic matter contained in chemical waste liquid in the fluidized bed system.
[0013] Beneficial effects: 1. The inner layer of the catalytic material of the present invention is an aerogel body loaded with metal active sites, which has well-developed internal pores, lower density than ordinary catalysts, and is easy to fluidize. 2. The outer layer of the catalytic material of the present invention is a molecular sieve film, which makes the material have good hydrophobicity and is not easy to deactivate in an environment rich in water molecules. 3. The double-layer structure of the catalytic material of the present invention reduces the interference of the external environment on the active metal sites in the inner layer, and effectively protects the core oxidation area. 4. The catalytic material of the present invention makes the reaction cracking and oxidation processes orderly and controllable, and the heat released by the organic matter is transferred from the inside to the outside, which strengthens the outer layer cracking process and makes full use of energy. 5. The catalytic material of the present invention realizes the organic coupling of catalytic cracking and catalytic oxidation in a high humidity environment and a gas-solid fluidized state, greatly reduces the reaction energy consumption and the macroscopic pyrolysis temperature through heat complementation, and provides support for the efficient and low-energy pyrolysis of waste liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a comparison diagram of the effects of removing COD from wastewater by the embodiments of the present invention and the comparative examples.
[0015] Figure 2 It is a diagram of expansion ratios of the embodiments of the present invention and the comparative examples under different air flow rates.
[0016] Figure 3 This is a scanning electron microscope image of Example 1 of the present invention.
[0017] Figure 4 It is a scanning electron microscope image of the comparative example. DETAILED DESCRIPTION
[0018] The present invention designs a manganese-cerium aerogel multifunctional catalytic material. The inner layer of the catalyst is an aerogel body loaded with metal active sites, and its internal pores are well developed, the density is controllable, lower than that of ordinary catalysts, and easy to fluidize. The outer layer is a molecular sieve film, which makes the material have good hydrophobicity and is not easy to deactivate in an environment rich in water molecules. At the same time, the double-layer structure reduces the interference of the external environment on the active metal sites in the inner layer, and effectively protects the core oxidation area. Organic macromolecules are cracked into small organic molecules at the acid sites of the outer layer of the catalyst, and continue to migrate inward to the inner layer through the pores. In the active oxygen environment of the active sites in the inner layer, they undergo intense oxidation combustion and release a large amount of heat. The heat is transferred from the inside to the outside, which strengthens the cracking process of the outer layer and makes full use of the energy. The multifunctional catalyst realizes the organic coupling of catalytic cracking and catalytic oxidation in a high humidity environment and a gas-solid fluidized state, greatly reduces the reaction energy consumption and the macroscopic pyrolysis temperature through heat complementation, and provides support for the efficient and low-energy pyrolysis of waste liquid.
[0019] Example 1
[0020] (1) Add 17.38g tetraethyl orthosilicate (TEOS), 19.16g anhydrous ethanol and 7.48g deionized water to a beaker, stir magnetically for 30 minutes to mix evenly, then drop 1mol / L dilute hydrochloric acid, adjust the pH to 2-3, and hydrolyze in a 40℃ water bath for 2h to obtain silica sol. (2) Dissolve 0.35g manganese acetate tetrahydrate and 0.32g cerium nitrate hexahydrate in 5mL deionized water, mix well and add to the above silica sol, continue stirring for 30 minutes, add 2.5mol / L dilute ammonia water to adjust the pH to between 6-8, and let stand at room temperature to obtain gel. (3) Stir 10 mL of tetraethyl orthosilicate and 40 mL of anhydrous ethanol for 15 minutes to prepare an aging solution, pour it into the above gel, and age it in a water bath at 50°C for 24 hours. After that, replace it with n-hexane at 40°C for 10 hours, and then dry it at 60°C, 80°C, 100°C, 120°C, and 150°C at normal pressure for 2 hours each. Place it in a muffle furnace at 550°C for 5 hours to obtain a metal-loaded silicon aerogel, grind it into powder for use. (4) Disperse the above aerogel powder in acetic acid solution, stir it at room temperature for 30 minutes, and etch the metal oxide on the surface of the aerogel. Wash the obtained sample with deionized water until the filtrate is neutral, and finally dry it in an oven at 100°C for 12 hours. (5) 6.79 g of tetrapropylammonium hydroxide (TPAOH) and 4 g of urea (urea) were dissolved in 90.10 g of deionized water, and 0.69 g of aluminum isopropoxide (AIP) was added and stirred at room temperature for 2 h. The aerogel powder was sprayed with this solution and allowed to stand at room temperature for 12 h. The mixture was then transferred to a polytetrafluoroethylene reactor liner, placed in an oven at 180 ° C for hydrothermal crystallization for 48 h. The mixture was subsequently washed, filtered, and dried in an oven at 100 ° C for 8 h. The catalyst material was finally obtained by heat preservation in a muffle furnace at 500 ° C for 5 h to remove the template.
[0021] Example 2
[0022] (1) Add 17.38g tetraethyl orthosilicate (TEOS), 19.16g anhydrous ethanol and 7.48g deionized water to a beaker, stir magnetically for 30 minutes to mix evenly, then drop 1mol / L dilute hydrochloric acid, adjust the pH to 2-3, and hydrolyze in a 40℃ water bath for 2h to obtain silica sol. (2) Dissolve 0.35g manganese acetate tetrahydrate and 0.32g cerium nitrate hexahydrate in 5mL deionized water, mix well and add to the above silica sol, continue stirring for 30 minutes, add 2.5mol / L dilute ammonia water to adjust the pH to between 6-8, and let stand at room temperature to obtain gel. (3) Stir 10 mL of tetraethyl orthosilicate and 40 mL of anhydrous ethanol for 15 minutes to prepare an aging solution, pour it into the gel prepared in (2), and age it in a water bath at 50°C for 24 hours. After aging, replace it with n-hexane at 40°C for 10 hours, and then dry it at 60°C, 80°C, 100°C, 120°C, and 150°C at normal pressure for 2 hours each. Place it in a muffle furnace at 550°C for 5 hours to obtain a metal-loaded silicon aerogel, grind it into powder for use. (4) Disperse the above aerogel powder in acetic acid solution, stir it at room temperature for 30 minutes, and etch the metal oxide on the surface of the aerogel. Wash the obtained sample with deionized water until the filtrate is neutral, and finally dry it in an oven at 100°C for 12 hours. (5) 6.79 g of tetrapropylammonium hydroxide (TPAOH) and 4 g of urea (urea) were dissolved in 90.10 g of deionized water, and 0.69 g of aluminum isopropoxide (AIP) was added and stirred at room temperature for 2 h. The aerogel powder was sprayed with this solution and allowed to stand at room temperature for 12 h. The mixture was then transferred to a polytetrafluoroethylene reactor liner, placed in an oven at 150 ° C for hydrothermal crystallization for 72 h. The mixture was subsequently washed, filtered, and dried in an oven at 100 ° C for 8 h. Finally, the catalyst material was obtained by heat preservation in a muffle furnace at 500 ° C for 5 h to remove the template.
[0023] Example 3
[0024] (1) Add 17.38g tetraethyl orthosilicate (TEOS), 19.16g anhydrous ethanol and 7.48g deionized water to a beaker, stir magnetically for 30 minutes to mix evenly, then drop 1mol / L dilute hydrochloric acid, adjust the pH to 2-3, and hydrolyze in a 40℃ water bath for 2h to obtain silica sol. (2) Dissolve 0.35g manganese acetate tetrahydrate and 0.32g cerium nitrate hexahydrate in 5mL deionized water, mix well and add to the above silica sol, continue stirring for 30 minutes, add 2.5mol / L dilute ammonia water to adjust the pH to between 6-8, and let stand at room temperature to obtain gel. (3) Stir 10 mL of tetraethyl orthosilicate and 40 mL of anhydrous ethanol for 15 minutes to prepare an aging solution, pour it into the gel prepared in (2), and age it in a water bath at 50°C for 24 hours. After aging, replace it with n-hexane at 40°C for 10 hours, and then dry it at 60°C, 80°C, 100°C, 120°C, and 150°C at normal pressure for 2 hours each. Place it in a muffle furnace at 550°C for 5 hours to obtain a metal-loaded silicon aerogel, grind it into powder for use. (4) Disperse the above silicon aerogel powder in acetic acid solution, stir it at room temperature for 30 minutes, and etch the metal oxide on the surface of the aerogel. Wash the obtained sample with deionized water until the filtrate is neutral, and finally dry it in an oven at 100°C for 12 hours. (5) 6.79 g of tetrapropylammonium hydroxide (TPAOH) and 4 g of urea (urea) were dissolved in 90.10 g of deionized water, and 0.69 g of aluminum isopropoxide (AIP) was added and stirred at room temperature for 2 h. The aerogel powder was sprayed with this solution and allowed to stand at room temperature for 12 h. The mixture was then transferred to a polytetrafluoroethylene reactor liner, placed in an oven at 120 ° C for hydrothermal crystallization for 36 h. The mixture was subsequently washed, filtered, and dried in an oven at 100 ° C for 8 h. The catalyst material was finally obtained by heat preservation in a muffle furnace at 500 ° C for 5 h to remove the template.
[0025] Comparative Example
[0026] Weigh 0.8 g of manganese acetate tetrahydrate and 0.72 g of cerium nitrate hexahydrate and add them to a beaker, then add 40 mL of deionized water to the beaker, stir magnetically for 30 min until the salt is completely dissolved, then add 11.4 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 50 to the solution, continue stirring for 12 h, ultrasonicate for 15 min, then transfer the mixture to an oven and dry at 80 ° C for 12 h, finally place the sample in a muffle furnace and keep it at 500 ° C for 3 h to obtain a conventional molecular sieve supported catalyst, grind it into powder for later use.
[0027] Examples and Comparative Examples Performance Test
[0028] (Waste liquid COD removal rate test) Taking the self-prepared high-concentration phenol-containing simulated waste liquid as the target pollutant, the potassium dichromate method was used to test its initial COD, and then the materials prepared in Examples 1, 2, 3 and the comparative example were used as catalysts, filled into the reaction tube, and the heating program was started. The temperature was set to 350°C. After the reaction temperature was reached, air was introduced into the reaction tube from the bottom at a rate of 500mL / min, and the phenol-containing waste liquid was input into the reaction tube through a micro-injection pump at a rate of 10mL / h. At the same time, the terminal condensation device of the reaction system was opened, the condensate was collected and its COD was tested, compared with the initial COD and the COD removal rate was calculated. In addition, the program was set to 350°C, 360°C, 370°C, 380°C, 390°C, and 400°C, respectively, and the other steps were the same as above. The experiment was carried out and the COD was tested. The COD removal effects of the four materials at different temperatures are shown in the figure. Figure 1 As shown in the figure, it can be seen that in this reaction system, Examples 1, 2, and 3 are better than the comparative examples in terms of COD removal effect under different temperature conditions. In addition, the COD removal rate of the comparative example at 400°C just barely reaches the level of the example at 350°C, which indicates that the energy released by the oxidation of organic molecules in the inner layer is transferred to the outer layer, which supplements the energy for the cracking process of the outer layer and makes more full use of the energy, thereby reducing the reaction energy consumption and the macroscopic pyrolysis temperature, reflecting the advantages of the catalyst of the example in terms of high efficiency and low energy.
[0029] (Expansion ratio) Take 20g of the materials prepared in Examples 1, 2, 3 and the comparative example respectively, put them into a reaction tube, and then introduce air from the bottom of the reaction tube at a flow rate of 200mL / min, 400mL / min and 600mL / min respectively, and record their expansion conditions (such as Figure 2 As shown in the figure, under different gas flow rates, the expansion ratio of the embodiment is much greater than that of the comparative example, so the embodiment is easier to fluidize than the comparative example.
[0030] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. For ordinary technicians in this technical field, after knowing the contents recorded in the present invention, they can make several equivalent changes and substitutions without departing from the principle of the present invention. These equivalent changes and substitutions should also be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a manganese-cerium aerogel multifunctional catalytic material, characterized in that: The preparation steps include: (a) stirring tetraethyl orthosilicate, ethanol and water evenly, wherein the molar ratio of tetraethyl orthosilicate, ethanol and water is n(TEOS):n(EtOH):n(H2O)=1:(3-12):(3-8), adjusting the pH to 2-3, and then hydrolyzing to obtain silica sol; (b) dissolving two metal salts, manganese acetate and cerium nitrate, in water, wherein the corresponding oxides formed by the metal salts after calcination account for 2wt.%-30wt.% of the mass of the aerogel carrier, and then adding the metal salts to the silica sol after mixing, stirring, adjusting the pH to 6-8, and standing at room temperature to obtain a gel; (c) preparing an aging solution with tetraethyl orthosilicate and ethanol, wherein the volume ratio is V(ETOH) / V(TEOS)=(4-10):1, pouring the solution into the gel for aging, and then replacing it with n-hexane, and then gradient drying, and then calcining and keeping warm after completion. , obtaining a metal-loaded silicon aerogel; (d) immersing the above aerogel in an acetic acid solution and stirring, etching the metal oxide on the surface of the aerogel, washing the obtained sample with deionized water until the filtrate is neutral, and drying in an oven; (e) dissolving tetrapropylammonium hydroxide and urea in water and adding aluminum isopropoxide and stirring at room temperature, wherein the molar ratio of aluminum isopropoxide, tetrapropylammonium hydroxide, water, and urea is n(AIP):n(TPAOH):n(H2O):n(urea)=1:(5-20):(800-3000):(20-80), spraying the obtained solution with aerogel powder, standing at room temperature, and then transferring the mixture to a polytetrafluoroethylene reactor liner, loading it into the reactor and placing it in an oven for hydrothermal crystallization, followed by washing, filtering, drying, and calcining to obtain an aerogel molecular sieve composite multifunctional catalytic material loaded with manganese and cerium.
2. The method for preparing the manganese-cerium aerogel multifunctional catalytic material according to claim 1, characterized in that: In the step (a), the molar ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is (TEOS):n(EtOH):n(H2O)=1:4:4; the reagent for adjusting pH is 0.1-1 mol / L dilute hydrochloric acid; the hydrolysis temperature is 25-60°C, and the hydrolysis time is 0.5-5h.
3. The method for preparing the manganese-cerium aerogel multifunctional catalytic material according to claim 1, characterized in that: The reagent for adjusting pH in step (b) is 0.1-2.5 mol / L dilute ammonia water.
4. The method for preparing the manganese-cerium aerogel multifunctional catalytic material according to claim 1, characterized in that: The volume ratio of the aging solution in step (c) is V (ETOH) / V (TEOS) = 4:1; the aging temperature is 25-70°C, and the aging time is 24-72h; the replacement temperature is 25-60°C, and the time is 9-24h; the gradient drying temperature is 2-4 points within 50-200°C, and the drying time at each temperature point is 1-4h; the calcination temperature is 400-700°C, and the insulation time is 4-6h.
5. The method for preparing the manganese-cerium aerogel multifunctional catalytic material according to claim 1, characterized in that: In the step (d), the stirring time is 20-120 minutes; the drying temperature is 60-120° C., and the drying time is 8-12 hours.
6. The method for preparing the manganese-cerium aerogel multifunctional catalytic material according to claim 1, characterized in that: In the step (e), the molar ratio of aluminum isopropoxide, tetrapropylammonium hydroxide, ionized water and urea is n(AIP):n(TPAOH):n(H2O):n(urea)=1:10:1500:40; the stirring time is 1-24h; the standing time at room temperature is 3-15h; the hydrothermal temperature is 80-180°C, and the hydrothermal time is 9-72h; the drying temperature is 80-120°C, and the drying time is 8-12h; the calcination temperature is 400-600°C, and the calcination time is 3-6h.
7. The manganese-cerium aerogel multifunctional catalytic material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the manganese-cerium aerogel multifunctional catalytic material according to claim 7 in cracking and oxidizing organic matter contained in chemical waste liquid in a fluidized bed system.
Citation Information
Patent Citations
Composite aerogel functional material, and preparation method and application thereof
CN111659323A
Ozone catalytic system composite aerogel, and preparation method and application thereof
CN111659324A
Composite aerogel as well as preparation method and application thereof
CN113842922A
Pt-coated Beta zeolite molecular sieve as well as preparation method and application thereof
CN116689022A